A Comparative Study of Npas in Private Sector Banks in India with Special Reference to ICICI Bank and HDFC Bank - Jain, Jainendra; Banerjee, Sudip (Journal of Advanced Research in Humanities and Social Sciences, 2022)
Indian Economy heavily depends on Banking Sector. Commercial Banks provide finances personal, business as well as industries. The Indian banking system is currently facing numerous issues as a result of growing NPAs. This paper focusing on the NPA study of two largest private sector banks in India. Two banks selected for this research ICICI and HDFC Bank. This research will study the bank business, profitability and NPAs of these banks from the period of 2012-2022. How to cite this article: Jain J, Banerjee S. A Comparative Study of Npas In Private Sector Banks in India with Special Reference to Icici Bank and HDFC Bank. J Adv Res Humani Social Sci 2022; 9(2): 17-25.